2018
DOI: 10.1111/camh.12308
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent self‐harm prevention and intervention in secondary schools: a survey of staff in England and Wales

Abstract: Background Adolescent self‐harm is a major public health concern. To date there is a limited evidence‐base for prevention or intervention, particularly within the school setting. To develop effective approaches, it is important to first understand the school context, including existing provision, barriers to implementation, and the acceptability of different approaches. Methods A convenience sample of 222 secondary schools in England and Wales were invited to participate in a survey, with a 68.9% (n = 153) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 38 publications
1
26
0
10
Order By: Relevance
“…Our study's findings corroborated with others around concerns of the age appropriateness of topics such as self-harm (Evans et al, 2019), indicating that delivery by professionals could be beneficial. The Green Paper on transforming children's mental health services (DOH & DFE, 2017) advised that all schools are allocated funding to develop Mental Health Support Teams as well as a designated senior lead for mental health.…”
Section: Ethical Implications and Parental Consentsupporting
confidence: 88%
“…Our study's findings corroborated with others around concerns of the age appropriateness of topics such as self-harm (Evans et al, 2019), indicating that delivery by professionals could be beneficial. The Green Paper on transforming children's mental health services (DOH & DFE, 2017) advised that all schools are allocated funding to develop Mental Health Support Teams as well as a designated senior lead for mental health.…”
Section: Ethical Implications and Parental Consentsupporting
confidence: 88%
“…Thus, as expected, the school staff and social workers in the present study suggested the inclusion of adolescent mental health issues in the social work and teacher training curricula and as part of social workers' and teachers' continuing professional development training programmes. Among other things, such in-service and preservice staff training should address the fear related to the misconception that talking about self-harm or suicide 'places the idea to try out the behaviour into the heads of young people' [45], and the need to avoid separating self-harm neatly into 'suicidal' and 'non-suicidal' [46][47][48][49]. This suggestion of stakeholder training is imperative, as studies have shown that the training of key stakeholders and adult gatekeepers is critical to the supportive roles these adults play towards improving the mental health of children and adolescents [50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Both education professionals and young people suggest that self-harm should be a priority issue to address in schools [ 32 , 33 ]. However, education professionals feel ill-equipped to address it [ 34 ]. The recent UK government Green Paper ‘Transforming Children and Young People’s Mental Health Provision’ [ 35 ] has laid out plans to develop a system of greater integration between the health and education sectors in the provision of mental health support for young people.…”
Section: Introductionmentioning
confidence: 99%